Augmented Reality (AR) Educational Media for the Prevention of the Three Major Sins in Education at Elementary Schools - Komang Alex Pramuditha Poerniawan; I Nengah Eka Mertayasa; I Nyoman Indhi Wiradika (Jurnal Media dan Teknologi Pendidikan, 2025)
The increasing prevalence of bullying, intolerance, and sexual violence in elementary schools indicates inadequate preventive efforts supported by innovative and technology-responsive educational media. This condition underscores the urgency of developing informative and engaging educational media to raise students’ awareness in preventing the Three Major Sins of Education. The purpose of this development research is to develop an Augmented Reality (AR) product as an educational medium to prevent the 3 Major Sins of Education in elementary schools and to describe the responses of students and teachers to the AR product. The type of research used is Research and Development (R & D) with the Multimedia Development Life Cycle (MDLC) model as a framework for developing multimedia products consisting of the stages of Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The results of this development research are in the form of an AR website assisted by Assmblr EDU called EduAR VIA, which has undergone content expert testing with a score of 1.00 with the criteria “Very Valid”, and a media expert test with a score of 1.00 with the criteria “Very Valid”, as well as a user response test showing a “Very Positive” qualification with the criteria “Very Good” or the developed media is able to increase students' interest in understanding the material on the 3 Major Sins in Education. Thus, the development of the Augmented Reality product has yielded valid results and positive responses, making it a relevant alternative educational medium with the potential to optimize education and foster positive character development in students.